Test–retest reliability of four sensory measures in people with multiple sclerosis. Issue 1 (March 2015) - Uszynski, Marcin; Purtill, Helen; Coote, Susan
<x xml:space="preserve">Abstract</x> This study investigated the test–retest reliability of the Neurothesiometer (NT), Verbal Analogue Scale for sensation (VAS), Erasmus modifications to the Nottingham Sensory assessment (EmNSA) and Semmes–Weinstein monofilaments (SWM) in people with multiple sclerosis (MS). A random sample of 34 people with MS who walked with or without an assistive device participated in this study. Participants were tested twice with the NT, VAS, EmNSA and SWM, 1 week apart. For categorical data, Cohen's kappa (Κ), percentage agreement (P0) and prevalence-adjusted bias-adjusted kappa (PABAK) were used. For continuous data, intraclass correlation coefficients [ICC (3, 1)] with 95% confidence intervals (95% CI), Bland–Altman plots and standard error of measurement (SEM) were calculated. The ICC values for NT were good, being the highest for the plantar aspect of the heel (ICC=0.92, 95% CI 0.85–0.96, SEM=4.24). Good ICC values were obtained for VAS questions on numbness, pins and needles and temperature and were supported by low SEM. Κ values for SWM were poor, ranging from 0.11 to 0.46 for the upper limb and 0.12 to 0.29 for the lower limb. Findings for EmNSA need further verification because of a possible ceiling effect in this test. The NT and VAS assessments for sensation had good test–retest reliability and should be considered for measuring changes in sensation in ambulatory people with MS. In contrast, findings from EmNSA and SWM revealed either questionable or poor test–retest reliability, suggesting that these two measures need further investigation.